Resistencia bacteriana de Escherichia coli uropatogénica en población nativa amerindia Kichwa de Ecuador - Guamán, William M. (2017)
Context: uropathogenic Escherichia coli (ECUP) is one of the main etiologic agents in uncom-plicated urinary tract infections (UTIs),(70-95%). The end point of antibiotic therapy is a full clinical and microbiological response. Objective: to identify bacterial resistance profiles to firstline antibiotics, used to treat uncomplicated UTI’s within indigenous communities in Ecuador, where the empiric treatment approach is based mainly on the use of trime-thoprim/sulfamethoxazole, ampicillin and ciprofloxacin.Methods: a total of 335 urine samples were collected and analysed during a four-month period (February- May 2016) in Zumbahua, Colta and Guamote. The samples were incubated for 24 and 48 hours in Eosin Methylene Blue (EMB) and subsequently identified at the genus and species level by biochemical tests. The Kirby-Bauer method (disc diffusion) was performed for phenotypic profiling of antibiotic susceptibility, and for the minimum inhibitory concentration (MIC), Vitek 2 broth micro-dilution was used. The double disk method was used for the identification of extended spectrum beta-lactamases (ESBL).Results: 90/335 (26,9%) urine samples were compatible with ITU (significant count of ≥105 colony forming units cfu/ml). The most frequently microorganism recov-ered was E.coli (n=75; 83,3%). The antibiotic resistance found in E. coli was trime-thoprim/sulfamethoxazole 56,7%; 52,5% to ampicillin; 43.3% to nalidixic acid; 32.5% to ciprofloxacin; 28.3% to norfloxacin; 25% to levofloxacin; 15.85% to cefazolin; 17.5% to cefoxitin, 15%;                                                        to cefuroxime; 15% to ceftazidime, cefotaxime, and ceftriaxone; 15% to cefepime; 7,5% to nitrofurantoin and 1,7% to phosphomycin. Seven extended spectrum betalactamases (ESBL) isolates were identified.Conclusion: these results drive to the recommendation of not using ampicillin, trimethoprim/sulfamethoxazole, nor quinolones in the area studied. We recommend empirical therapy with phosphomycin or nitrofurantoin